Relasi, Interaksi dan Komunikasi Interpersonal Dokter-Pasien dalam Pelayanan Kesehatan - Joko Febriantoro (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2020)
Introduction: The doctor-patient relationship is based on good quality of communication and interaction with thepatient, so that it not only can help speed up the healing process, but also make the patient feel comfortable sincethe first visit to the health service. When dealing with pediatric patients, the ability to build a relationship of mutualtrust is done with a more open, honest attitude and understanding what they are feeling. Aim of study: This studyaims to see a real picture of the relationships, interactions and interpersonal communication between doctors andpatients in health care. Method: This study uses a qualitative descriptive study where data is obtained throughinterview transcripts, field observation data notes and photo documentation. A total of 7 participants were obtainedthrough a purposive sampling technique on pediatricians who are accustomed to engaging in effective relationships,interactions and communication with pediatric patients, families and introductors. Data were then analyzed usingthe Miles and Huberman method. Results and Discussions: The results showed three important aspects related torelations, interactions and interpersonal communication between patient physicians in terms of educating,providing entertainment and strengthening patient motivation while in health care. Conclusions: Effectiveinterpersonal communication requires the optimal role of the doctor as a communicator to deliver messages to thepatient or family or patient introduction. In addition, the communication relationship between doctor and patientshould be therapeutic, especially in patients who are still children so that they do not feel scared while in healthcare, which in turn has an impact on the development of patient recovery.